Lactate concentration and creatine kinase activity after 110-m and 400-m hurdles races - Kryściak, Jakub; Podgórski, Tomasz; Eichler, Adam (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. 110-m and 400-m hurdles races are based on anaerobic energy metabolism which can induce muscle fatigue and muscle fiber damage. The most common biochemical parameters used in controlling athletes’ training loads and post-exercise fatigue are blood lactate (La) concentration and creatine kinase (CK) activity. Aim of Study. The aim of the study was to determine and compare runners’ biochemical response after 110-mand 400-m hurdles races. The influence of warm-up before both races was taken into consideration. Material and Methods. Eight male hurdlers took part in this research. They were subjected to two test exercises: a 110-m and a 400-m hurdles race. During each test, pre-warm-up, post-warm-up, and post-exercise capillary blood from a fingertip was collected to determine the La concentration and CK activity. Furthermore, during both sprint runs the athletes’ time (to the nearest 0.01 s) and heart rate (HR) were measured. Results. Each kind of exercise test increased the La concentration and CK activity. More significant changes of both biochemical parameters occurred after the 400-m race. Furthermore, after each warm-up significant increases of La and CK levels were observed. After the 400-m hurdles race higher HR values were noted (184.50 ± 8.32 compared to 177.50 ± 11.14 after the 110-m sprint). Conclusions. Both specialist warm-up and 110 and 400 meters hurdles races lead to significant changes in athletes’ physiological and biochemical blood parameters. La concentration and CK activity demonstrate greater muscle fatigue and muscle fiber damage after a 400-m than a 110-m hurdles race
Keywords: anaerobic exercise; hurdling; warm-up; muscle damage; muscle fatigue